2015
DOI: 10.1007/s00429-015-1121-9
|View full text |Cite
|
Sign up to set email alerts
|

The timing of language learning shapes brain structure associated with articulation

Abstract: We compared the brain structure of highly proficient simultaneous (two languages from birth) and sequential (second language after age 5) bilinguals, who differed only in their degree of native-like accent, to determine how the brain develops when a skill is acquired from birth versus later in life. For the simultaneous bilinguals, gray matter density was increased in the left putamen, as well as in the left posterior insula, right dorsolateral prefrontal cortex, and left and right occipital cortex. For the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 51 publications
3
35
0
Order By: Relevance
“…Whole‐brain analyses were conducted on 334 brain scans using general linear modeling to determine differences in brain structure relative to AoA. Because previous studies have found neuroanatomical effects associated with AoA by conducting analyses that treat AoA as categorical (i.e., Berken et al, ; Kaiser et al, ; Klein et al, ; Mohades et al, 2012) and continuous (i.e., Klein et al, ; Nichols & Joanisse, ; Wei et al, ), this study used both group comparisons (ANOVA) and regression analyses (in which AoA was treated as a continuous variable). Analyses of cortical thickness, volume, and density were conducted.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Whole‐brain analyses were conducted on 334 brain scans using general linear modeling to determine differences in brain structure relative to AoA. Because previous studies have found neuroanatomical effects associated with AoA by conducting analyses that treat AoA as categorical (i.e., Berken et al, ; Kaiser et al, ; Klein et al, ; Mohades et al, 2012) and continuous (i.e., Klein et al, ; Nichols & Joanisse, ; Wei et al, ), this study used both group comparisons (ANOVA) and regression analyses (in which AoA was treated as a continuous variable). Analyses of cortical thickness, volume, and density were conducted.…”
Section: Resultsmentioning
confidence: 99%
“…Whole-brain analyses were conducted on 334 brain scans using general linear modeling to determine differences in brain structure Berken et al, 2016b;Kaiser et al, 2015;Klein et al, 2014;Mohades et al, 2012) and continuous (i.e., Klein et al, 2014;Nichols & Joanisse, 2016;Wei et al, 2015), this study used both group comparisons (ANOVA) and regression analyses (in which…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cortical thickness begins to decrease at the rate of 1–2% each year, beginning around 10 years of age . The connections between the rest of the brain and the prefrontal cortex—the core executive centers—begin to myelinate at 12 years of age and continue throughout this period . By middle to late adolescence, teenagers have fewer connections than they did as children, but these connections are selectively stronger within specific brain networks.…”
Section: Drivers Of Developmentmentioning
confidence: 99%
“…4 The connections between the rest of the brain and the prefrontal cortex-the core executive centersbegin to myelinate at 12 years of age and continue throughout this period. 31 By middle to late adolescence, teenagers have fewer connections than they did as children, but these connections are selectively stronger within specific brain networks. This period is marked by the maturation of two competing systems: the low-road emotional system, including the amygdala and nucleus accumbens, and the high-road executive system, including the prefrontal cortex and bilateral parietofrontal network.…”
Section: First 2 Years Of Life: a Nurturing Caregiver Is The Drivermentioning
confidence: 99%